2019
DOI: 10.23910/ijbsm/2019.10.1.1947
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bio-accelerated Farming against Conventional Farming System on Green Gram (Vigna radiata L.) under Rainfed Condition: Adaptive Management Enhances the Resilience to Climate Change

Abstract: The field experiments was conducted at the Instructional Farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Coochbehar, West Bengal, India during 2011-2012. The objective was to assess the effect of chemical free bio-accelerated and conventional farming system on growth, yield attributes, yield, nutrients uptake, quality and microbial population of green gram. The farm is situated at 26 o 19'86"N latitude and 89 o 23'53"E longitude at an elevation of 43.0 m above mean sea level. Results revealed that the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Dehydrogenase (µg/ml) 2.771 increased the plant height (304 cm), number of branches/plant (40), leaf area/plant (18075 dm 2 ) of pigeon pea over control. Dahal et al [10] found that the maximum number of branches/plant in mungbean was recorded in bio-accelerated farming wherein Jiwamrita was used as compared to conventional farming wherein synthetic fertilizers were used. Combination treatment of soil and foliar application of Jiwamrita significantly affected the number of root nodules (94) over alone foliar application and alone soil application (86 and 90, respectively) of Jiwamrita.…”
Section: Growth Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dehydrogenase (µg/ml) 2.771 increased the plant height (304 cm), number of branches/plant (40), leaf area/plant (18075 dm 2 ) of pigeon pea over control. Dahal et al [10] found that the maximum number of branches/plant in mungbean was recorded in bio-accelerated farming wherein Jiwamrita was used as compared to conventional farming wherein synthetic fertilizers were used. Combination treatment of soil and foliar application of Jiwamrita significantly affected the number of root nodules (94) over alone foliar application and alone soil application (86 and 90, respectively) of Jiwamrita.…”
Section: Growth Attributesmentioning
confidence: 99%
“…The application of Jiwamrita improved the physical, chemical and biological properties of soil, besides improving the efficiency of applied manure [9]. It was also reported to be a catalytic agent to promote activity of microorganisms resulting in healthy and nutrient rich soil [10]. Earlier work by Galindo et al, [11] reported that the use of the fermented liquid as organic source of nutrient @ 3% foliar spray recorded significantly higher growth and yield of blackgram.…”
Section: Introductionmentioning
confidence: 99%